Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=\(x^3.\left(\frac{-5}{4}x^2y\right)\)=\(x^5\).\(\left(\frac{-5}{4}\right)y\)
-Bậc là: 6
-Hệ số:\(\frac{-5}{4}\)
B=\(\left(\frac{-3}{4}x^5y^4\right).\left(xy^2\right).\left(\frac{-8}{9}\right)\)\(x^2y^5\)
=\(\frac{2}{3}.x^8.y^{11}\)
-Bậc là: 19
-Hệ số:\(\frac{2}{3}\)
C=\(\frac{1}{6}x\left(2y^3\right)^2.\left(-9x^5y\right)\)
=\(\frac{1}{6}x\left(4.y^6\right).\left(-9x^5y\right)\)
=-6.\(x^6\).\(y^7\)
-Bậc là: 13
-Hệ số: -6
A=\(\left(-\frac{5}{4}\times\frac{2}{5}\right)\times\left(x^3x^2x^3\right)\times\left(yy^4\right)\)
A=\(-\frac{1}{2}x^8y^5\)
B=\(\left(-\frac{3}{4}\times-\frac{8}{9}\right)\times\left(x^5xx^2\right)\times\left(y^4y^2y^5\right)\)
B=\(\frac{2}{3}x^8y^{11}\)
1.
\(-3x^5y^4+3x^2y^3-7x^2y^3+5x^5y^4\)
\(=(-3x^5y^4+5x^5y^4)+(3x^2y^3-7x^2y^3)\)
\(=2x^5y^4-4x^2y^3\)
2.
\(\frac{1}{2}x^4y-\frac{3}{2}x^3y^4+\frac{5}{3}x^4y-x^3y^4\)
\(=(\frac{1}{2}x^4y+\frac{5}{3}x^4y)-(\frac{3}{2}x^3y^4+x^3y^4)\)
\(=\frac{13}{6}x^4y-\frac{5}{2}x^3y^4\)
3.
\(5x-7xy^2+3x-\frac{1}{2}xy^2\)
\(=(5x+3x)-(7xy^2+\frac{1}{2}xy^2)\)
\(=8x-\frac{15}{2}xy^2\)
4.
\(\frac{-1}{5}x^4y^3+\frac{3}{4}x^2y-\frac{1}{2}x^2y+x^4y^3\)
\(=(\frac{-1}{5}x^4y^3+x^4y^3)+(\frac{3}{4}x^2y-\frac{1}{2}x^2y)\)
\(=\frac{4}{5}x^4y^3+\frac{1}{4}x^2y\)
5.
\(\frac{7}{4}x^5y^7-\frac{3}{2}x^2y^6+\frac{1}{5}x^5y^7+\frac{2}{3}x^2y^6\)
\(=(\frac{7}{4}x^5y^7+\frac{1}{5}x^5y^7)+(-\frac{3}{2}x^2y^6+\frac{2}{3}x^2y^6)\)
\(=\frac{39}{20}x^5y^7-\frac{5}{6}x^2y^6\)
6.
\(\frac{1}{3}x^2y^5(-\frac{3}{5}x^3y)+x^5y^6=(\frac{1}{3}.\frac{-3}{5})(x^2.x^3)(y^5.y)+x^5y^6\)
\(=\frac{-1}{5}x^5y^6+x^5y^6=\frac{4}{5}x^5y^6\)
a) M=\(\frac{-1}{9}\)x4y3(2xy2)2=\(\frac{-1}{9}\)x4y3(4x2y4)=\(\frac{-1}{9}\)x6y7
b) y=\(\frac{-x}{3}\)=> x=-3y
mà x+y=2
=>-3y+y=2 <=> -2y=2 => y=-1 => x=-3y=-3*-1=3
Thay x=3; y=-1 vào M...=>M=\(\frac{-1}{9}\)(36)(-17)=81
a,-200 x10 t10z3
b,\(\frac{-5}{4}\)x11 y5 z4
c,\(\frac{2}{15}\)x6 y6 z9
d,\(\frac{1}{7}\)x10 y6 z7
e,-4z6 y10 z6
\(\frac{81}{3^y}=9\)
\(3^y=9=3^2;y=2\)
3x =9 = 32
Vậy x = 2
\(8^3:4^4=\frac{8^3}{4^4}=\frac{\left(2^3\right)^3}{\left(2^2\right)^4}=\frac{2^9}{2^8}=2\)
a) 32
b)32
c) 83:44= (23)3:(22)4= 29:28=21